MARKETING PERFORMANCE IMPROVEMENT MODEL THROUGH DIGITAL INNOVATION OF BANKING PRODUCTS: MODERATION ROLE OF DIGITAL LITERACY - Faizal, Mohamad; Hurriyati, Ratih; Hendrayati, Heny; Sultan, Mokh. (Jurnal Riset Bisnis dan Manajemen, 2024)
This study aims to explore the improvement of marketing performance by digital service quality through digital innovation of banking products, with digital literacy moderation. The design of this study is an explanatory survey of 384 Bank Mandiri customers who use the Livin' by Mandiri application in Region VI/Java 1 under the West Java Regional Office. Data analysis is a descriptive and verification method using Partial Least Square (PLS). The findings are that Bank Mandiri's marketing performance can be implemented well through digital innovation of banking products, which is based on the quality of digital services, strengthened by digital literacy. The novelty is related to placing the Digital Innovation of Banking Product variable as a mediator, and Digital Literacy as a moderation. The implication is that Bank Mandiri needs to elaborate digital innovation of banking products to ensure the products and services align with customer expectations and needs in marketing performance.